Experimental Optimization of Biocement Formation: Alternative Countermeasure for Surface Erosion of Cut Slope - Gowthaman, S.; Nakashima, K.; Ebina, K.; Kawasaki, S. (University of Moratuwa., 2018)
The research work aims to assess the feasibility of introducing the microbial induced carbonate precipitation (MICP) as an alternative technique for surface stabilization of the cut slopes by augmenting potential indigenous ureolytic bacteria. A set of column solidification tests was conducted on embankment soil (Hokkaido expressway, Japan) to optimize the performance of bacteria regarding bacterial population of culture solution (optical density (OD600) from 1 to 6), and concentration of Ca2+ and urea in cementation solution (0.5 mol/L and 1 mol/L) at the temperature of 20C. The UCS of treated samples was estimated using needle penetrometer, and the microstructure of the treated specimens was observed using scanning electron microscope (SEM). The results reveal that the UCS of the specimen increases with increasing OD600 without any clogging within the samples. Treating the soil using 1 mol/L concentrated (Ca2+ and urea) cementation solution and bacterial culture with OD600 of 6 results the highest UCS of 7.5 MPa while achieving relatively a homogeneous solidification along the column profile. The micrographs of the treated specimen confirms that the rhombohedral calcium carbonate crystals formed within the pores of soil matrix, which has effectively bonded the adjacent soil particles, and contributed to enhance the strength significantly at the optimized treatment condition.
Keywords: Calcium carbonate; Cementation; Microbial induced carbonate precipitation (MICP); Surface stabilization; Ureolytic bacteria